A new method to measure rolling resistance in treadmill cycling - Henchoz, Y.; Crivelli, G.; Borrani, F.; Millet, G. P. (Journal of Sports Sciences, 2010)
The purpose of this study was to evaluate a new method of measuring rolling resistance in treadmill cycling and to establish its sensitivity and reproducibility. One participant was asked to keep a bicycle in equilibrium on a treadmill without pedalling at a constant speed of 5.56 m/s, which was held in place in the front by a dynamometer. For each condition, the method consisted of 11 measurements of the force required to hold the cycle at different treadmill slopes (0-10%, increment 1%). The coefficient of rolling resistance was calculated based on the forces applied to the bicycle in equilibrium. To test the sensitivity of the method, the bicycle was successively equipped with three tyre types (700 28, 700 23, 700 22) and inflation pressure was set at 150, 300, 600, 900, and 1100 kPa. To test the reproducibility of the method, a second experimenter repeated all measurements done with the 700 23 tyres. The method was sensitive enough to detect an effect of both tyre type and inflation pressure (P < 0.001: two-way ANOVA). The measurement of the coefficient of rolling resistance by two separate experimenters resulted in a small bias of 0.00029 (95% CI, -0.00011 to 0.00068). In conclusion, the new method is sensitive and reliable, as well as being simple and affordable.